Enhancement Of Structural Integrity On Apron And Soil Settlement Behavior At Kompleks Penghulu Ayer Hitam, Muar Structures - Chin, Darren Daniel; Tuan Chik, Tuan Norhayati (Journal of Structural Monitoring and Built Environment, 2024)
Concrete apron failure, often linked to soil settlement, presents significant challenges in civil engineering and infrastructure development. This study investigates the mechanisms contributing to apron deterioration, including cracking, spalling, and structural instability, with a focus on soil settlement behavior. Field studies and laboratory tests such as atterberg limit, grain size analysis, compaction test, and consolidation tests were conducted. Results show the soil has a moderate plasticity index (9.9%), is well-graded gravel (Cu=3.75, Cc=1.5), with an optimum moisture content of 14.5% and a rapid consolidation coefficient (12.74 m²/year). These findings inform recommendations for improved apron designs. Geogrids are proposed as an effective solution to enhance stability and durability, addressing the complex interaction between soil and concrete structures.